Modelling Anisotropic Behavior of AISI 304 Stainless Steel Sheet Using a Fourth-Order Polynomial Yield Function - Sener, Bora; Kilicarslan, Elif Sila; Firat, Mehmet (ELSEVIER SCIENCE BV, 2020)
Following the description of an orthotropic, non-quadratic, homogenous polynomial type yield criterion, its finite element (FE) implementation is presented for the purpose of sheet metal forming analysis using an explicit time integration scheme. Then the performance of the FE implementation is firstly investigated by means of tensile test simulations of AISI (304) stainless steel sheets, and directional variation of yield strength and anisotropy factors are predicted. Next, deep drawing simulations of rectangular cups are performed, and FE computed cup thickness and flange geometry are assessed with measurements. Comparisons in both deformation processes showed that a fourth-order polynomial criterion can accurately describe the anisotropic behavior of AISI (304) stainless steel sheets. (C) 2020 The Authors. Published by Elsevier Ltd.
Keywords: Polynomial type yield function; Finite element simulation; Rectangular cup drawing; AISI-304 steel sheet; CRITERION; Engineering; Materials Science